If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u + -20 = 14 Reorder the terms: -20 + 2u = 14 Solving -20 + 2u = 14 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 2u = 14 + 20 Combine like terms: -20 + 20 = 0 0 + 2u = 14 + 20 2u = 14 + 20 Combine like terms: 14 + 20 = 34 2u = 34 Divide each side by '2'. u = 17 Simplifying u = 17
| y=xp^2+p^2 | | 5x+132=6x-21+7x-1 | | (x+3)(x-9)(6-x)=0 | | x^2-x-1+3i=0 | | 3x+(2-4x)=4 | | 8/21k=1/3 | | y-aw=2w-1 | | 5-x/6=2x/3 | | -6y=-3x+18 | | X-3/5=2x/8 | | 4x/3=2/9 | | -9y+9x=18 | | 3x+5+2+4=19 | | 3(3.6x-5.4)-2.9x=-4(x-9.6) | | 123x+4= | | 0.2(4x-8.1)=2(3.2x-1.6) | | 8(x+2)=3y-x | | 3/(x^3-4x) | | 3.4(x-6)=-12.9 | | 2y+3x=-12 | | 2.3(x+3)=-9.66 | | 9a-54=0 | | ax-a(a+b)=-x-(-1+ab) | | (3p^-4)/(9p^7) | | 3-d+-2=4-2d+-4+7 | | 3/4(16x-8)=1/2(36x-7) | | 3/4(16x-8=1/2(36x-7) | | 5/6(2x-5)=1/3 | | 0.7x^2-0.7x+4.9=0.7 | | 4-6(2-8x)=3x+4(x-9) | | 3-(5x-4)=6+2(3x-1)+x | | cosx=8 |